2011
DOI: 10.1002/uog.7747
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic herniation of the liver (‘liver‐up’) is associated with predominant left heart hypoplasia in human fetuses with left diaphragmatic hernia

Abstract: K E Y W O R D S: ('liver-up') and Group II an intra-abdominal liver position ('liver-down'). Cardiac inflow and outflow diameter ratios and cardiac Z-scores were compared between the two groups. Results Eleven of the 15 Group I (liver-up) fetuses, but only three of the 17 Group II (liver-down) fetuses with left diaphragmatic hernia exhibited predominant left heart hypoplasia with disproportionately smaller left than right heart dimensions (P = 0.0036). In addition, 14 of the 15 Group I fetuses, but only five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
5
25
0
1
Order By: Relevance
“…It may be that a lower percentage of LH allows for improved pulmonary and left heart growth as a result of decreased mass effect on developing intrathoracic structures. This is consistent with previous findings as noted by Stressig and colleagues, who found that LHH is more commonly seen in those where LH is present . As noted in Stressig's article, we too observed that the presence of LH correlated to smaller postnatal mitral valve z‐scores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It may be that a lower percentage of LH allows for improved pulmonary and left heart growth as a result of decreased mass effect on developing intrathoracic structures. This is consistent with previous findings as noted by Stressig and colleagues, who found that LHH is more commonly seen in those where LH is present . As noted in Stressig's article, we too observed that the presence of LH correlated to smaller postnatal mitral valve z‐scores.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with left‐sided CDH, the fetal left heart structures are often compressed and found to be smaller than normal, resulting in varying degrees of left heart hypoplasia (LHH) . The presence of smaller left heart structures is thought to be secondary to impaired left heart filling from compression of the left heart by abdominal viscera within the thoracic cavity, distortion of the ductus venosus with alteration of streaming patterns, diminishing right‐to‐left intra‐cardiac shunting, reduced pulmonary venous return to the left heart due to pulmonary hypoplasia and pulmonary hypertension, and compression upon a preload‐deficient left ventricle by a hypertensive right ventricle . These combined factors result in a decrease of total blood flow through the left side of the heart, potentially leading to sub‐optimal growth of these structures as a result of altered fetal hemodynamics …”
Section: Introductionmentioning
confidence: 99%
“…Second, abdominal viscera displacement in CDH induces persistent mechanical compression of the left heart and creates a hemodynamic situation similar to that in chronic cardiac tamponade, with the result that cardiac diastolic dysfunction prevents sufficient left ventricle growth [20]. Finally, intrathoracic herniation of the liver (liverup), which presumably results from rerouting of the majority of the ductus venous and inferior vena cava flow towards the right side of the heart, is observed in the majority of fetuses with severe CDH and predominant left heart hypoplasia [14,21].…”
Section: Discussionmentioning
confidence: 97%
“…Liver herniation has also been suggested to have a direct impact on cardiac filling and hence output. Stressig et al [51] describe preferential streaming to the right heart in the presence of liver herniation in fetuses with left-sided CDH. Though their main interest was to study the impact on the left heart, it would mean that also in utero pulmonary hemodynamics might be different from those without liver herniation.…”
Section: Discussionmentioning
confidence: 99%